In situ Occurrence, Prevalence and Dynamics of Parvilucifera Parasitoids during Recurrent Blooms of the Toxic Dinoflagellate Alexandrium minutum - Alacid, Elisabet; Reñé, Albert; Camp, Jordi; Garcés, Esther (Frontiers in Microbiology, 2017)
Dinoflagellate blooms are natural phenomena that often occur in coastal areas, which in addition to their large number of nutrient-rich sites are characterized by highly restricted hydrodynamics within bays, marinas, enclosed beaches, and harbors. In these areas, massive proliferations of dinoflagellates have harmful effects on humans and the ecosystem. However, the high cell density reached during blooms make them vulnerable to parasitic infections. Under laboratory conditions parasitoids are able to exterminate an entire host population. In nature, Parvilucifera parasitoids infect the toxic dinoflagellate Alexandrium minutum during bloom conditions but their prevalence and impact remain unexplored. In this study, we evaluated the in situ occurrence, prevalence, and dynamics of Parvilucifera parasitoids during recurrent blooms of A. minutum in a confined site in the NW Mediterranean Sea as well as the contribution of parasitism to bloom termination. Parvilucifera parasitoids were recurrently detected from 2009 to 2013, during seasonal outbreaks of A. minutum. Parasitic infections in surface waters occurred after the abundance of A. minutum reached 104–105 cells L−1, suggesting a density threshold beyond which Parvilucifera transmission is enhanced and the number of infected cells increases. Moreover, host and parasitoid abundances were not in phase. Instead, there was a lag between maximum A. minutum and Parvilucifera densities, indicative of a delayed density-dependent response of the parasitoid to host abundances, similar to the temporal dynamics of predator-prey interactions. The highest parasitoid prevalence was reached after a peak in host abundance and coincided with the decay phase of the bloom, when a maximum of 38% of the A. minutum population was infected. According to our estimates, Parvilucifera infections accounted for 5–18% of the total observed A. minutum mortality, which suggested that the contribution of parasitism to bloom termination is similar to that of other biological factors, such as encystment and grazing.